Preparation and Evaluation of Palonosetron Hydrochloride Oral Thin Film (Bangladesh Pharmaceutical Journal, 2019)
The purpose of the current study was to develop a fast dissolving polymeric oral thin film containing palonosetron hydrochloride having good mechanical properties, fast disintegration, dissolution and good drug content uniformity. Solvent casting method was used to prepare the films. Compatibility between drugs and excipients were studied using FTIR and HPLC. Nine different formulations of film from F1 to F9 were prepared using different concentration of polymer A at drug-polymer A ratio (1:26), (1:28), (1:30), (1:32), (1:34), (1:36), (1:38), (1:40), (1:42) and at polymer A-plasticizer B of (65:10), (70:10), (75:10), (40:10), (42.5:10), (45:10), (47.5:10), (50:10), (52.5:10), respectively. The in vitro dissolution study was carried out in phosphate buffer (pH 6.8) at 37±0.5oC and 50 rpm using USP XXIV paddle method. Physicochemical evaluations of all the batches were performed including weight variation, thickness, folding endurance, pH, in vitro disintegration and drug release, FTIR and content uniformity test. Maximum and minimum drug dissolution were found in F6 (108.7%) and in F1 (98.5%), respectively. The maximum and minimum disintegration time were in F9 (43.8 sec) and F1 (25 sec), respectively which demonstrated that disintegration of the film was directly proportional to the polymer A and plasticizer B concentration. It is quite evident from the present research work that the film prepared using polymer A-plasticizer B were smooth, mechanically strong and easy to peel out. Among all the batches, formulation F5 showed best results with respect to disintegration (33 sec), drug dissolution (105%), content uniformity (98.51%) and folding endurance (731). Therefore, it can be said that combination of polymer A and plasticizer B can be prospectively used for the preparation of palonosetron hydrochloride oral thin film.Bangladesh Pharmaceutical Journal 22(2): 228-234, 2019